Pemanfaatan Penggunaan Media Digital dalam Pembelajaran PAI di Sekolah Berbasis Alam - Putri Susana Bela; Karimatul Hidayah; Ahmad Muliyadi; Nurman Nurman; Dessy Kurnia Mulyani (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
The integration of digital media in Islamic Education (PAI) teaching has become a significant advancement in educational practice, especially in today’s technology-driven era. This article examines various forms of digital tools and their benefits in PAI learning through a literature review. The research highlights how digital media can optimize learning outcomes, enrich the content of lessons, and increase students' enthusiasm for studying Islamic education. The findings suggest that tools like mobile apps, interactive videos, and online platforms can significantly enhance the teaching and learning process. The integration of digital media in Islamic Education (PAI) in schools that adopt nature-based learning approaches presents significant opportunities for improving education quality and engaging students. In the digital age, PAI education faces the challenge of attracting the attention of the millennial generation, who are already accustomed to technology. This article explores how digital media can serve as an innovative tool to boost millennial students' interest in learning PAI. The approach involves using mobile apps, interactive videos, and online platforms to create learning experiences that align with the learning styles of millennials. By leveraging the tech-savvy characteristics of millennials, the use of digital media in PAI classrooms can make the learning process more relevant and engaging. Moreover, the article emphasizes how digital media can stimulate discussions and encourage active participation, establishing a connection between PAI content and students' daily lives. The successful implementation of digital media to increase students' interest in PAI requires active involvement from educators in designing engaging content, facilitating online interactions, and continuously innovating their teaching methods. This article provides practical guidance for educators to effectively integrate digital media into their teaching practices, enhancing student engagement with PAI education